Exploring factors influencing depression among Polish nurses during the COVID-19 pandemic - Kamila Rachubińska; Mariusz Panczyk; Marcin Sygut; Przemysław Ustianowski; Elżbieta Grochans; Anna Maria Cybulska (Frontiers Media S.A., 2023)
ObjectivesThe COVID-19 pandemic has been recognized as an international public health emergency. The aim of our study was to identify contributors to nurses' depression.MethodsThis survey-based study was conducted in the Pomeranian Medical University Hospital no. 1 in Szczecin and involved 207 nurses. The following standardized research instruments were applied: the World Assumptions Scale, the Athens Insomnia Scale, the Impact of Event Scale - Revised, the Patient Health Questionnaire-9, the Generalized Anxiety Disorder, the Perceived Stress Scale, and a questionnaire of our own authorship.ResultsThe study showed that 72.95% of the subjects experienced severe stress, and 40.58% suffered from insomnia. In addition, 65.7% of the respondents had anxiety symptoms of varying degrees of severity, and 62.8% had depressive symptoms of mild to severe severity. The mean score on the IES-R scale, reflecting a psychological impact of the COVID-19 pandemic, was 34.25. The COVID-19 pandemic affected the psychological health of medical staff, particularly through increased stress and anxiety symptoms. Anxiety levels and insomnia significantly affect the prevalence of depression among nurses.ConclusionThe COVID-19 pandemic has been recognized as an international public health emergency. The COVID-19 pandemic affected the psychological health of medical staff, particularly through increased stress and anxiety symptoms. It is important to conduct further research after the COVID-19 pandemic has ended.